Tradition or oppression? the role of cultural norms in sexual violence against Queer communities - Kasa, Luvo (Edelweiss Applied Science and Technology, 2025)
This study explores the impact of cultural norms on sexual violence against queer individuals, focusing on African societies where traditional practices, heteronormativity, and patriarchy converge to marginalize non-heterosexual and non-cisgender identities. Drawing on intersectionality and queer affirmative theory, the research examines how cultural values shape perceptions of acceptable sexual behavior and reinforce systemic exclusion and violence. The study employs a mixed-methods approach, analyzing twenty peer-reviewed articles published between 2018 and 2023 through thematic and descriptive analysis. Findings reveal that cultural practices such as initiation rites and rigid gender roles often exclude queer individuals, exposing them to psychological, physical, and emotional harm. Colonial legacies, religious ideologies, and a lack of inclusive policies further intensify the erasure of queer identities. The research underscores the critical need to challenge oppressive norms while respecting cultural identity, highlighting the role of social work in fostering inclusive, community-based interventions. Education, community engagement, and policy advocacy are essential for reforming traditions that perpetuate gender-based violence. Ultimately, the study calls for a transformation of cultural narratives to embrace diversity, protect human rights, and affirm queer identities in African societies.